Penilaian Tingkat Kognitif Siswa Kelas VII-1 SMPN 3 Mataram Berdasarkan Revisi Taksonomi Bloom dalam Pembelajaran Proyek Penguatan Profil Pelajar Pancasila (P5) - Setiawati, Komang Sulis; Ariani, Siti; Noviantari, Mardiana; Putri, Ni Made Ayu Amanda Indriani; Jayadin; Herianto, Edy Herianto (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
This study aims to determine the cognitive level of students in class Vll-1 SMPN 3 Mataram based on the revision of Bloom's taxonomy in P5 learning. This study uses a type of descriptive qualitative research. The data used are primary data and secondary data. The data collection techniques in this study are observation, interviews and documentation. The results of this study show that the P5 learning carried out by class Vll-1 chose the theme of sustainable lifestyle with a special theme of turning waste into blessings. To realize the project, there are four stages that are carried out, namely discovering is introducing and discussing issues related to waste problems in rivers and beaches, imagine is the stage of contemplating about waste, doing is the action stage of students making works from waste, and distributing is the last stage by holding work exhibitions and project evaluations. The abilities of students in class Vll-1 in the cognitive domain include the level of (a) knowledge, students give the same answers to questions given related to waste (b) understanding, students give different opinions in the diagram task (c) application, students apply steps to make waste into useful products (d) analysis, students describe clearly and concisely about waste sorting (e) evaluation, Students hold an exhibition of works and reflection projects (f) create, students produce products from recycled waste. The students' learning results showed that the level of creating students in class Vll-1 was at a fairly high level because it was able to produce outputs in P5 learning in the form of handicrafts from waste including cracker clothes, sack clothes, plates from ale-ale glasses, flower vases, plastic bags, and lamp decorations.